Inclusion of Hearing Impaired Children in Inclusive School: A Survey to Determine Teacher’s Attitude - Hifsa Batool, Adila Khanam, Hina Akbar (JIE, 2021)
Education for all and inclusion of disabled students in mainstream schools is the topic of interest for all the researchers of this technological world. The present study was conducted in the Punjab, Pakistan, to find out and compare teacher’s attitude towards inclusion of hearing impaired in inclusive school.